The Position of Visum Et Repertum as Evidence in Proving Criminal Cases in Indonesia - Firmansyah, Muhammad; Simangunsong, Frans (Universitas Jabal Ghafur, 2024)
This study aims to examine and analyze the position of visual evidence et repertum in proving criminal cases in Indonesia. In this study is normative juridical research as well as a statutory approach and a coceptual approach. The results of this study show that evidence in criminal cases is very important. One of the most important things in the evidence visum et repertum to reveal the cause and effect of a criminal case incident, in accordance with the purpose in criminal law is to find material truth. Visum et repertum is included in valid evidence under article 184 of the Code of Criminal Procedure, namely letter evidence and also expert testimony. To clearly establish the cause and effect of a criminal act, it is necessary to provide evidence visum et repertum against a number of crimes, including crimes that violate decency, against life, persecution, and negligence resulting in the death of a person or convict, injury to others. Other crimes include knowing the age of the victim or perpetrator of the crime. To find out the cause and effect of a criminal act that occurred, as well as to collect information and seek the objective truth of a criminal act related to the relationship between the act and the consequences caused, visum et repertum in proving criminal cases in Indonesia is very important. Keywords : Criminal case, Evidence, Visum et repertum